Inequality, marketisation and the left: Schools policy in England and Sweden. (24th March 2015) - Hicks, Timothy
Abstract It is argued in this article that the marketisation of schools policy has a tendency to produce twin effects: an increase in educational inequality, and an increase in general satisfaction with the schooling system. However, the effect on educational inequality is very much stronger where prevailing societal inequality is higher. The result is that cross‐party political agreement on the desirability of such reforms is much more likely where societal inequality is lower (as the inequality effects are also lower). Counterintuitively, then, countries that are more egalitarian – and so typically thought of as being more left‐wing – will have a higher likelihood of adopting marketisation than more unequal countries. Evidence is drawn from a paired comparison of English and Swedish schools policies from the 1980s to the present. Both the policy history and elite interviews lend considerable support for the theory in terms of both outcomes and mechanisms.